Robots and automated manufacture - Billingsley, J. (John) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1985)
The book reviews developments in the following fields: steering mechanism for legged robot;use of simulation in th off-line programming of robot; off-line programming of a robot from a CAD system; application of rule based method to inspection and quality control in a manufacturing process; automatic location editing of assembly robot program; industrial robot's dynamic analysis using decentralised control via kinematics; collision avoidance; flexible automated assembly system; robot force sensing; automatic visual inspection; visual feedback control for orienting parts in the assembly robot cycle; low cost vision for welding robots and automated welding machines; and high-speed pattern recognition system for robotic application.